PERANCANGAN DAN PEMBUATAN GATING SYSTEM PADA PRODUK CLAMP SADDLE DENGAN PROSES PENGECORAN LOGAM SAND CASTING - Sylvano Nehemia Leksono; Fais Hamzah; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Abstract – PT. Aneka Adhilogam Karya is a national private company engaged in the sand-casting industry supplying its products to the Perusahaan Daerah Air Minum (PDAM) Indonesia. One of the products of piping supporting components manufactured is Clamp Saddle. Many of these products still have casting defects, such as gas porosity and shrinkage. Gating system is one of the most crucial factors to determine the quality of cast products. It is necessary to design a gating system for Clamp Saddle products. Then the casting simulation using ProCast 2018 needs to be done to get an optimal design and detect the presence of defect shrinkage or gas porosity. Furthermore, the sand casting process is carried out, and radiographic testing is carried out to detect defects in the inside of the Clamp Saddle product. The results of the study obtained agating system design with a pattern size of 400 mm x 335 mm then analyzed defects using ProCast 2018 on the variable total shrinkage porosity and air entrainment so that optimal results were obtained. Clamp Saddle product results from sand casting experiments were tested using radiography test(RT) to detect shrinkage or gas porosity and found some gas porosity but were still tolerable because of their small size of about 1 mm then they were few in number and were not gathered together